Integrated bioethanol and biomanure production from potato waste. (March 2016) - Chintagunta, Anjani Devi; Jacob, Samuel; Banerjee, Rintu
Graphical abstract: Highlights: Integrated production of bioethanol and biomanure from potato waste was attempted. Optimum yield of ethanol was 6.18% (v/v) and 9.30% (v/v) with co-cultures. Residual waste utilization as biomanure with NPK enrichment of 2:1:1. Abstract: Disposal of potato processing waste and the problem of pollution associated with it is a vital issue that is being faced by the potato processing plants. The conventional peeling methods presently followed in the processing plants for removing the potato peel, also result in the loss of some portion of the mash which is rich in starch. Indiscriminate discharge of the waste causes detrimental effects in the environment, so this problem can be resolved by successful utilization of the waste for the generation of value added products. Hence, the present work focuses on integrated production of bioethanol and biomanure to utilize the waste completely leading to zero waste generation. The first part of the work describes a comparative study of ethanol production from potato peel and mash wastes by employing co-culture of Aspergillus niger and Saccharomyces cerevisiae at various incubation time (24–120 h) instead of application of enzymes. The solid state fermentation of potato peel and mash inoculated with co-culture, resulted in bioethanol production of 6.18% (v/v) and 9.30% (v/v) respectively. In the second part of the work, the residue obtained after ethanol production was inoculated with seven different microorganisms ( Nostoc muscorum, Fischerella muscicola, Anabaena variabilis, Aulosira fertilissima, Cylindrospermum muscicola, Azospirillium lipoferum, Azotobacter chroococcum ) and mixture of all the organisms in equal ratio for nitrogen (N), phosphorous (P) and potassium (K) enrichment. Among them, A. variabilis was found to enrich N, P and K content of the residue by nearly 7.66, 21.66 and 15 fold than that of the initial content, ultimately leading to improved N:P:K ratio of approximately 2:1:1. The application of simultaneous saccharification and fermentation (SSF) for the conversion of potato waste to ethanol and enrichment of residue obtained after ethanol production with microorganisms to be used as manure envisages environmental sustainability.